Hydrogel catalytic membrane containing double atomic sites and confined water purification application
By introducing hydrogel catalytic membranes and cross-flow filtration modes with diatomic sites into traditional single-atom catalysts, the problems of high cost, low load and difficulty in regeneration of traditional catalysts are solved, and efficient organic pollutant degradation and catalysts are achieved Resource regeneration.
Patent Information
- Application Number
- CN202411344906.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional single-atom catalysts are costly, low loading, easy to agglomerate, difficult to regenerate catalysts, and the reaction kinetics of heterogeneous persulfate catalytic systems are limited by the mass transfer efficiency of the diffusion layer, resulting in excessive oxidant usage and high system cost. .
Using a hydrogel catalytic film containing diatomic sites, the polysaccharide polymer cast film liquid with blended cocatalysts is cross-linked with a transition metal ion solution of redox pairs to form a high-strength hydrogel film and combine it with The cross-flow filtration mode realizes rapid degradation of organic pollutants and regenerates and utilizes transition metals through hydrothermal reactions.
The metal loading is significantly improved, the energy cost and reaction time are reduced, the organic pollutant degradation rate is achieved from 60% to 100%, and the resource recycling and utilization of catalysts is realized.
Smart Images

Figure CN119237014A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hydrogel catalytic membrane containing diatomic sites and a confined water purification application, belonging to the field of functional materials and advanced oxidation water treatment. Background Art
[0002] Organic waste is a major cause of water pollution. There are many types of organic pollutants in water, with complex components and toxicity, which poses great harm to the environment and human body. Traditional wastewater treatment methods include physical adsorption, chemical, biological, electrochemical, etc. However, it is very difficult to treat organic wastewater that is difficult to degrade, and it can no longer meet the increasingly high environmental protection and process requirements. Advanced persulfate oxidation processes (PS-AOPs) have attracted widespread attention from researchers due to their excellent oxidation efficiency. PS-AOPs oxidizes through free radicals (such as SO4· - ) and non-radical oxidation (such as singlet oxygen and direct electron transfer) activation of persulfate can effectively destroy the structure of organic pollutants. Due to its long radical lifetime (30-40μs), high oxidation potential (2.5-3.1V) and wider pH response range, persulfate-based advanced oxidation processes are regarded as highly promising technologies. In recent years, single atom catalysts (SACs) have the greatest utilization efficiency for each metal atom and have excellent catalytic activity and selectivity in persulfate activation. For the single-atom level of metal particles, SACs exhibit high specific surface area and surface energy, and their unique properties enable SACs to overcome traditional limitations of catalytic kinetics and catalytic activity.
[0003] Traditional methods for synthesizing single-atom catalysts include template method, sol-gel method, ball milling method and chemical vapor deposition method. These processes usually involve long-term sintering at high temperatures, which brings challenges related to large energy consumption and thermal regeneration of catalyst activity. In addition, in addition to the high cost and long time of the synthesis process, the effective loading of traditional single-atom catalysts is often low, basically below 5%. Therefore, how to increase the overall metal site loading of the catalyst while avoiding the appearance of a large number of metal clusters as much as possible is also a key challenge faced by the synthesis of traditional single-atom catalysts.
[0004] On the other hand, although many studies have demonstrated that the persulfate activation system has a high oxidation efficiency under laboratory conditions, in the traditional reaction mode, due to the poor diffusion and mass transfer efficiency of organic matter and oxidant (the thickness of the diffusion layer is greater than 100 microns), it is necessary to add excessive oxidant to the system. Specifically, the dosage of persulfate is about 100 times the concentration of organic matter, which further increases the cost of the system and limits its practical application. Therefore, in the case of low oxidant dosage, how to improve the reaction kinetics of heterogeneous persulfate catalytic system is crucial. A large number of studies have shown that the reaction form based on confined catalysis can significantly enhance the reaction kinetics and reduce the amount of system oxidant because the diffusion layer of the interface can be compressed to quickly improve the mass transfer performance of the system. However, the current assembly based on single-atom confined materials is often filtered by dispersion onto the microfiltration membrane substrate, and the composite membrane has weak mechanical strength, which greatly limits further promotion and use as well as recycling and regeneration.
[0005] Chen Min et al. first proposed a method for removing organic pollutants by combining alginate-based heterogeneous catalytic hydrogel membrane with peroxymonosulfate cross-flow activation [Advanced Materials, 2024, 2311416]. This method prepared a metal-alginate hydrogel membrane. Due to the pressure-driven field of the cross-flow mode, the anchored metal complex provides abundant reaction sites for peroxymonosulfate and organic matter under the spatial confinement of a small diffusion layer, thereby removing SO4· - Theoretical calculations show that the reactivity of cobalt alginate structured hydrogels is superior to that of other types of metal (Ni, Cu and Zn) based hydrogels according to the peroxymonosulfate adsorption energy barrier.
[0006] As basic research and application technologies for various materials become increasingly sophisticated, the materials community has shifted from early single research and development efforts such as replacing toxic and scarce elements, energy conservation and emission reduction, and recycling technologies to recognizing the trend towards material life cycle engineering that must be based on a full life cycle approach. This requires starting from material product design and resource acquisition, and oriented to the entire life cycle. On the basis of a correlated quantitative analysis of material performance, resource / energy consumption, and environmental impact, it pursues the optimization of the entire industrial chain, and through continuous technological innovation and process optimization in material manufacturing, use, recycling and other links, effectively reduces the comprehensive environmental load of material products throughout their life cycle.
[0007] In view of the high cost, low loading, easy agglomeration and difficulty in regenerating the catalyst of the traditional single-atom catalyst, the present invention reports a hydrogel catalytic membrane containing diatomic sites and a confined water purification application. First, the polysaccharide polymer casting liquid of the blended catalyst is scraped on the carrier, and then cross-linked in two transition metal ion solutions that can constitute a redox couple to obtain a hydrogel catalytic membrane containing diatomic sites. The carrier and the hydrogel membrane are fixed in the membrane pool assembly of the cross-flow filtration as the catalytic interface, and the rapid mass transfer of peroxides and organic matter in the limited hydrogel catalytic membrane interface diffusion layer is achieved by regulating the pressure field, thereby quickly degrading organic pollutants in a very short time. The used hydrogel catalytic membrane is dissolved with a sodium citrate aqueous solution, and the transition metal in the hydrogel catalytic membrane is converted into a metal oxide by a hydrothermal reaction and separated and purified, which can realize resource recycling. The catalytic membrane of the present invention has the characteristics of a large metal loading, which effectively improves the restriction of the low metal content of the traditional single-atom catalyst. The hydrogel catalytic membrane has broad application prospects in the fields of sewage treatment and environmental protection. Summary of the invention
[0008] In view of the shortcomings of the prior art, the technical problems that the present invention intends to solve are the high cost, low loading, easy agglomeration and difficulty in regenerating of traditional single-atom catalysts. The technical solution of the present invention to the above-mentioned problems is to provide a hydrogel catalytic membrane containing diatomic sites and its application in confined water purification.
[0009] The present invention provides a hydrogel catalytic membrane containing diatomic sites and a confined water purification application, which is characterized by comprising the following steps:
[0010] a) preparing a mixture of a polysaccharide polymer with a mass percentage concentration of 1% to 5% and a promoter with a mass percentage concentration of 0.5% to 5% as a casting solution, and defoaming the mixture for later use; the polysaccharide polymer is any one of sodium alginate, carboxymethyl chitosan, and carboxymethyl cellulose, or a mixture of two or more thereof; the promoter is any one of molybdenum disulfide, tungsten disulfide, and cobalt disulfide, or a mixture of two or more thereof;
[0011] b) preparing a mixed aqueous solution of transition metal ions constituting a redox couple as a coagulation bath, wherein the transition metal ions are Co 2+ / Ni 2+ , Cu 2+ / Mn 2+ , Fe 3+ / Mn 2+ , Fe 3+ / Cu 2+ 、Co 2+ / Cu 2+ ,La 3+ / Cu 2+ ,La3+ / Co 2+ Any one of the following; the total mass percentage concentration of transition metal ions in the coagulation bath is 0.5% to 5%, and the molar ratio of the two transition metal ions constituting the redox couple is 1:9 to 9:1;
[0012] c) selecting a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, and coating the casting solution obtained in step a) on the non-woven fabric with a scraper under a winding transmission device to form a liquid film on the non-woven fabric, and then immersing the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), and after sufficient cross-linking, washing away the transition metal ions on the surface with deionized water to obtain a hydrogel catalytic membrane containing diatomic sites, and winding the hydrogel catalytic membrane together for standby use;
[0013] d) using a cross-flow filtration device to perform limited water purification on organic pollutants, the cross-flow filtration device consisting of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve and a membrane pool; cutting the hydrogel catalytic membrane containing diatomic sites obtained in step c) and loading it into the membrane pool, adding a mixed aqueous solution of organic pollutants and peroxides into the stock liquid tank; using a hydrogel catalytic membrane containing diatomic sites that can form a rich redox couple, combined with a cross-flow filtration mode, solves the problems of mass transfer limitation and catalyst fixed position. Under pressure drive, this mode only requires extremely low energy cost and extremely short reaction time to achieve rapid degradation of organic pollutants, and the degradation rate of organic pollutants reaches 60% to 100% in 2 to 5 minutes;
[0014] e) dissolving the hydrogel catalytic membrane with reduced catalytic performance after repeated use with a sodium citrate aqueous solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by hydrothermal reaction and separating and purifying them, dissolving them with dilute hydrochloric acid,
[0015] The transition metal ion solution is obtained and the coagulation bath in step b) is re-prepared, thereby realizing the recycling of resources.
[0016] The peroxide described in the present invention is one or more of hydrogen peroxide, peroxymonosulfate, peroxydisulfate, and peracetic acid. The organic pollutant described is one or more of sulfamethazine, methylisothiazolinone, tetracycline, and bisphenol A. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 It is a schematic diagram of the preparation process and recovery process of a hydrogel catalytic membrane containing diatomic sites provided in Example 1;
[0019] Figure 2 This is a single-atom phase transmission electron microscopy morphology photograph corresponding to a hydrogel film containing diatomic sites provided in Example 1;
[0020] Figure 3 It is a cobalt atom X-ray absorption fine structure spectrum corresponding to a hydrogel film containing diatomic sites provided in Example 1;
[0021] Figure 4 The nickel atom X-ray absorption fine structure spectrum corresponding to a hydrogel film containing diatomic sites provided in Example 1;
[0022] Figure 5 This is a performance diagram of a hydrogel membrane containing diatomic sites provided in Example 1 for removing different organic pollutants in a confined catalytic mode;
[0023] Figure 6 This is a water purification performance effect diagram of a hydrogel membrane containing diatomic sites provided in Example 2 under different peroxide corresponding confined catalytic modes;
[0024] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0025] The preparation and application process of the present invention is shown in Figure 1 Specific embodiments of the present invention are described below, but the present invention is not limited to the embodiments.
[0026] Example 1.
[0027] a) preparing a mixture aqueous solution of 3% sodium alginate and 5% molybdenum disulfide as a casting solution, and defoaming it for later use;
[0028] b) Prepare transition metal ions Ni that can form redox pairs 2+ / Co 2+ The mixed aqueous solution is used as a coagulation bath, wherein the total mass percentage concentration of transition metal ions in the coagulation bath is 5%, and the transition metal ions Ni that can constitute a redox pair 2+ / Co 2+ The molar ratio is 1:9;
[0029] c) Select a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, and use a scraper to apply the casting solution obtained in step a) on the non-woven fabric under a winding transmission device to form a liquid film on the non-woven fabric, and then immerse the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), and after sufficient cross-linking, use deionized water to rinse off the Ni on the surface. 2+ / Co 2+ transition metal ions, a hydrogel catalytic film containing Ni / Co diatomic sites was obtained (the transmission electron microscopy photo of its single-atom phase morphology is shown in Figure 2 The results of X-ray absorption fine structure spectroscopy are shown in Figure 3 and Figure 4 ), winding the hydrogel catalytic membrane together for standby use;
[0030] d) performing limited water purification on different types of pollutants (sulfamethoxazole, methylisothiazolinone, tetracycline, bisphenol A) by a cross-flow filtration device, wherein the cross-flow filtration device is composed of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve and a membrane pool; cutting the Ni / Co diatomic site hydrogel catalytic membrane obtained in step c) and loading it into the membrane pool, adding organic matter (10 ppm) and peroxymonosulfate (0.2 mmol L -1 ) mixed aqueous solution; using a hydrogel catalytic membrane containing Ni / Co diatomic sites that can form redox couples, combined with a cross-flow mode, the problems of mass transfer limitation and catalyst fixation are solved. Under pressure drive, the cross-flow filtration mode only requires extremely low energy cost and extremely short reaction time (5 minutes) to achieve rapid degradation of pollutants (>95%), and has excellent removal effects on various types of pollutants (see Figure 5 );
[0031] e) dissolving the hydrogel catalytic membrane with reduced catalytic performance after repeated use with a sodium citrate aqueous solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by hydrothermal reaction and separating and purifying them, and dissolving them with dilute hydrochloric acid to obtain transition metal Ni 2+ / Co 2+ The aqueous solution of ions is used to re-prepare the coagulation bath in step b), thereby realizing the recycling of resources.
[0032] Example 2.
[0033] a) preparing a mixture aqueous solution of a polymer with a mass percentage concentration of 1% (wherein the mass fraction of sodium alginate and carboxymethyl chitosan is 1:1) and a molybdenum disulfide with a mass percentage concentration of 0.5% as a casting solution, and defoaming the mixture for later use;
[0034] b) Prepare transition metal ions Ni that can form redox pairs 2+ / Co 2+The mixed aqueous solution is used as a coagulation bath, wherein the total mass percentage concentration of transition metal ions in the coagulation bath is 5%, and the transition metal ions Ni that can constitute a redox pair 2+ / Co 2+ The molar ratio is 3:7;
[0035] c) Select a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, and use a scraper to apply the casting solution obtained in step a) on the non-woven fabric under a winding transmission device to form a liquid film on the non-woven fabric, and then immerse the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), and after sufficient cross-linking, use deionized water to rinse off the Ni on the surface. 2+ / Co 2+ transition metal ions, to obtain a hydrogel catalytic membrane containing Ni / Co diatomic sites, and to roll up the hydrogel catalytic membrane for later use;
[0036] d) using a cross-flow filtration device to investigate the limited water purification application of bisphenol A in different peroxides (hydrogen peroxide, peroxymonosulfate, peroxydisulfate, and peracetic acid), wherein the cross-flow filtration device is composed of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve, and a membrane pool; cutting the Ni / Co diatomic site-containing hydrogel catalytic membrane obtained in step c) and loading it into the membrane pool, adding bisphenol A (10 ppm) and peroxide (0.2 mmol L -1 ) mixed aqueous solution; using a hydrogel catalytic membrane containing Ni / Co diatomic sites that can form redox pairs, combined with a cross-flow mode, the problems of mass transfer limitation and catalyst fixation are solved. Under pressure drive, the cross-flow filtration mode only requires extremely low energy cost and extremely short reaction time (2 minutes) to activate different types of peroxides to achieve rapid degradation of pollutants (60-99%, see Figure 6 );
[0037] e) dissolving the hydrogel catalytic membrane with reduced catalytic performance after repeated use with a sodium citrate aqueous solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by hydrothermal reaction and separating and purifying them, and dissolving them with dilute hydrochloric acid to obtain transition metal Ni 2+ / Co 2+ The aqueous solution of ions is used to re-prepare the coagulation bath in step b), thereby realizing the recycling of resources.
[0038] Example 3.
[0039] a) preparing a mixture aqueous solution of 5% by mass concentration of carboxymethyl chitosan and 5% by mass concentration of tungsten disulfide as a casting solution, and defoaming it for later use;
[0040] b) Prepare transition metal ions Cu that can form redox pairs2+ / Mn 2+ The mixed aqueous solution is used as a coagulation bath, wherein the total mass percentage concentration of transition metal ions in the coagulation bath is 5%, and the transition metal ions Cu that can constitute a redox pair 2+ / Mn 2+ The molar ratio is 9:1;
[0041] c) Selecting a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, using a scraper to apply the casting solution obtained in step a) to the non-woven fabric under a winding transmission device to form a liquid film on the non-woven fabric, and then immersing the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), and after sufficient cross-linking, using deionized water to rinse off the Cu on the surface 2+ / Mn 2+ transition metal ions, obtaining a hydrogel catalytic membrane containing Cu / Mn diatomic sites, and winding the hydrogel catalytic membrane together for use;
[0042] d) using a cross-flow filtration device to perform a limited water purification application on tetracycline, wherein the cross-flow filtration device is composed of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve and a membrane pool; cutting the hydrogel catalytic membrane containing Cu / Mn diatomic sites obtained in step c) and loading it into the membrane pool, adding tetracycline (10 ppm) and peroxymonosulfate (0.2 mmol L -1 ) mixed aqueous solution; using a hydrogel catalytic membrane containing Cu / Mn diatomic sites that are rich in redox couples, under pressure-driven, cross-flow filtration mode only requires extremely low energy cost and extremely short reaction time to achieve rapid degradation of tetracycline, and the degradation rate of tetracycline reaches 100% in 2 minutes;
[0043] e) dissolving the hydrogel catalytic membrane with reduced catalytic performance after repeated use with a sodium citrate aqueous solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by hydrothermal reaction and separating and purifying them, and dissolving them with dilute hydrochloric acid to obtain transition metal Cu 2+ / Mn 2+ The aqueous solution of ions is used to re-prepare the coagulation bath in step b), thereby realizing the recycling of resources.
[0044] Example 4.
[0045] a) preparing a mixture aqueous solution of 3% by mass concentration of carboxymethyl cellulose and 2% by mass concentration of cobalt disulfide as a casting solution, and defoaming it for later use;
[0046] b) Prepare transition metal ions Fe that can form redox pairs 3+ / Mn 2+The mixed aqueous solution is used as a coagulation bath, wherein the total mass percentage concentration of transition metal ions in the coagulation bath is 4%, and the transition metal ions Fe that can constitute a redox pair 3+ / Mn 2+ The molar ratio is 1:1;
[0047] c) Select a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, and use a scraper to apply the casting solution obtained in step a) to the non-woven fabric under a winding transmission device to form a liquid film on the non-woven fabric, and then immerse the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), and after sufficient cross-linking, use deionized water to rinse off the Fe on the surface. 3+ / Mn 2+ transition metal ions, obtaining a hydrogel catalytic membrane containing Fe / Mn diatomic sites, and winding the hydrogel catalytic membrane together for use;
[0048] d) performing a limited water purification application on bisphenol A by a cross-flow filtration device, wherein the cross-flow filtration device is composed of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve and a membrane pool; cutting the hydrogel catalytic membrane containing Fe / Mn diatomic sites obtained in step c) and loading it into the membrane pool, adding bisphenol A (10 ppm) and peroxydisulfate (0.2 mmol L -1 ) mixed aqueous solution; using a hydrogel catalytic membrane containing Fe / Mn diatomic sites that are rich in redox couples, under pressure-driven, cross-flow filtration mode requires only extremely low energy cost and extremely short reaction time to rapidly degrade bisphenol A, with a degradation rate of 99% for bisphenol A within 3 minutes;
[0049] e) dissolving the hydrogel catalytic membrane with reduced catalytic performance after repeated use with a sodium citrate aqueous solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by hydrothermal reaction and separating and purifying them, and dissolving them with dilute hydrochloric acid to obtain transition metal Fe 3+ / Mn 2+ The aqueous solution of ions is used to re-prepare the coagulation bath in step b), thereby realizing the recycling of resources.
[0050] Example 5.
[0051] a) preparing a mixture aqueous solution of 0.5% by mass concentration of carboxymethyl cellulose, 2.5% by mass concentration of sodium alginate, and 1% by mass concentration of molybdenum disulfide as a film casting solution, and defoaming the mixture for later use;
[0052] b) Prepare transition metal ions Fe that can form redox pairs 3+ / Cu 2+The mixed aqueous solution is used as a coagulation bath, wherein the total mass percentage concentration of transition metal ions in the coagulation bath is 3%, and the transition metal ions Fe that can constitute a redox pair are 3+ / Cu 2+ The molar ratio is 2:8;
[0053] c) Select a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, and use a scraper to apply the casting solution obtained in step a) to the non-woven fabric under a winding transmission device to form a liquid film on the non-woven fabric, and then immerse the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), and after sufficient cross-linking, use deionized water to rinse off the Fe on the surface. 3+ / Cu 2+ transition metal ions, obtaining a hydrogel catalytic membrane containing Fe / Cu diatomic sites, and winding the hydrogel catalytic membrane together for use;
[0054] d) using a cross-flow filtration device to perform limited water purification on sulfamethoxazole, wherein the cross-flow filtration device is composed of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve and a membrane pool; cutting the hydrogel catalytic membrane containing Fe / Cu diatomic sites obtained in step c) and loading it into the membrane pool, adding sulfamethoxazole (10 ppm) and peracetic acid (0.2 mmol L -1 ) mixed aqueous solution; using a hydrogel catalytic membrane containing Fe / Cu diatomic sites that are rich in redox couples, under pressure-driven, cross-flow filtration mode only requires extremely low energy cost and extremely short reaction time to quickly degrade sulfamethoxazole, and the degradation rate reaches 92% after 2 minutes;
[0055] e) dissolving the hydrogel catalytic membrane with reduced catalytic performance after repeated use with a sodium citrate aqueous solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by hydrothermal reaction and separating and purifying them, and dissolving them with dilute hydrochloric acid to obtain transition metal Fe 3+ / Cu 2+ The aqueous solution of ions is used to re-prepare the coagulation bath in step b), thereby realizing the recycling of resources.
[0056] Example 6.
[0057] a) preparing a mixture aqueous solution of 1% carboxymethyl chitosan, 2.5% sodium alginate and 2% molybdenum disulfide as a casting solution, and defoaming the mixture for later use;
[0058] b) Prepare transition metal ions Co that can form redox pairs 2+ / Cu 2+The mixed aqueous solution is used as a coagulation bath, wherein the total mass percentage concentration of transition metal ions in the coagulation bath is 4%, and the transition metal ions Co that can constitute a redox pair 2+ / Cu 2+ The molar ratio is 3:7;
[0059] c) Select a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, and use a scraper to apply the casting solution obtained in step a) to the non-woven fabric under a winding transmission device to form a liquid film on the non-woven fabric, and then immerse the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), and after sufficient cross-linking, use deionized water to rinse off the Co 2+ / Cu 2+ transition metal ions, to obtain a hydrogel catalytic film containing Co / Cu diatomic sites, and to roll up the hydrogel catalytic film for later use;
[0060] d) performing a limited water purification application on bisphenol A by a cross-flow filtration device, wherein the cross-flow filtration device is composed of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve and a membrane pool; cutting the hydrogel catalytic membrane containing Co / Cu diatomic sites obtained in step c) and loading it into the membrane pool, adding bisphenol A (10 ppm) and peroxymonosulfate (0.2 mmol L -1 ) mixed aqueous solution; using a hydrogel catalytic membrane containing Co / Cu diatomic sites that can form a redox couple, under pressure-driven, cross-flow filtration mode only requires extremely low energy cost and extremely short reaction time to achieve rapid degradation of bisphenol, and the degradation rate of bisphenol A reaches 99% in 2 minutes;
[0061] e) dissolving the hydrogel catalytic membrane with reduced catalytic performance after repeated use with a sodium citrate aqueous solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by hydrothermal reaction and separating and purifying them, and dissolving them with dilute hydrochloric acid to obtain transition metal Co 2+ / Cu 2+ The aqueous solution of ions is used to re-prepare the coagulation bath in step b), thereby realizing the recycling of resources.
[0062] Example 7.
[0063] a) preparing a mixture aqueous solution of 1% by mass concentration of carboxymethyl chitosan, 2% by mass concentration of carboxymethyl cellulose, 1% by mass concentration of molybdenum disulfide, and 1% by mass concentration of cobalt disulfide as a casting solution, and defoaming it for standby use;
[0064] b) Prepare transition metal ions La that can form redox pairs 3+ / Cu 2+The mixed aqueous solution is used as a coagulation bath, wherein the total mass percentage concentration of transition metal ions in the coagulation bath is 2%, and the transition metal ions La that can constitute a redox pair 3+ / Cu 2+ The molar ratio is 4:6;
[0065] c) Selecting a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, using a scraper to apply the casting solution obtained in step a) to the non-woven fabric under a winding transmission device to form a liquid film on the non-woven fabric, and then immersing the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), after sufficient cross-linking, washing the surface La with deionized water. 3+ / Cu 2+ transition metal ions, to obtain a hydrogel catalytic film containing La / Cu diatomic sites, and to roll up the hydrogel catalytic film for later use;
[0066] d) performing a limited water purification application on bisphenol A and tetracycline by a cross-flow filtration device, wherein the cross-flow filtration device is composed of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve and a membrane pool; cutting the La / Cu diatomic site-containing hydrogel catalytic membrane obtained in step c) and loading it into the membrane pool, adding bisphenol A (10 ppm), tetracycline (10 ppm) and peroxymonosulfate (0.2 mmol L -1 ) mixed aqueous solution; using a hydrogel catalytic membrane containing La / Cu diatomic sites that can form a redox couple, under pressure-driven, cross-flow filtration mode only requires extremely low energy cost and extremely short reaction time to achieve rapid degradation of bisphenol A and tetracycline, with a degradation rate of 99% for bisphenol A and 99% for tetracycline in 2 minutes;
[0067] e) dissolving the hydrogel catalytic membrane with reduced catalytic performance after repeated use with a sodium citrate aqueous solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by hydrothermal reaction and separating and purifying them, and dissolving them with dilute hydrochloric acid to obtain transition metal La 3+ / Cu 2+ The aqueous solution of ions is used to re-prepare the coagulation bath in step b), thereby realizing the recycling of resources.
[0068] Example 8.
[0069] a) preparing a mixture aqueous solution of 3% sodium alginate and 1.5% molybdenum disulfide by mass concentration as a film casting solution, and defoaming it for later use;
[0070] b) Prepare transition metal ions La that can form redox pairs 3+ / Co 2+The mixed aqueous solution is used as a coagulation bath, wherein the total mass percentage concentration of transition metal ions in the coagulation bath is 0.5%, and the transition metal ions La that can constitute a redox pair 3+ / Co 2+ The molar ratio is 2:8;
[0071] c) Selecting a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, using a scraper to apply the casting solution obtained in step a) to the non-woven fabric under a winding transmission device to form a liquid film on the non-woven fabric, and then immersing the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), after sufficient cross-linking, washing the surface La with deionized water. 3+ / Co 2+ transition metal ions, to obtain a hydrogel catalytic film containing La / Co diatomic sites, and to roll up the hydrogel catalytic film for later use;
[0072] d) using a cross-flow filtration device to perform a limited water purification application on tetracycline, wherein the cross-flow filtration device is composed of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve and a membrane pool; cutting the La / Co diatomic site-containing hydrogel catalytic membrane obtained in step c) and loading it into the membrane pool, adding tetracycline (10 ppm) and hydrogen peroxide (0.1 mmol L -1 ) and peroxymonosulfate (0.1 mmol L -1 ) mixed aqueous solution; using a hydrogel catalytic membrane containing La / Co diatomic sites that are rich in redox couples, under pressure-driven, cross-flow filtration mode requires only extremely low energy cost and extremely short reaction time to rapidly degrade tetracycline, with a degradation rate of 99% for tetracycline in 2 minutes;
[0073] e) dissolving the hydrogel catalytic membrane with reduced catalytic performance after repeated use with a sodium citrate aqueous solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by hydrothermal reaction and separating and purifying them, and dissolving them with dilute hydrochloric acid to obtain transition metal La 3+ / Co 2+ The aqueous solution of ions is used to re-prepare the coagulation bath in step b), thereby realizing the recycling of resources.
Claims
1. A hydrogel catalytic membrane containing diatomic sites and its application in confined water purification, characterized in that The following steps are involved: a) preparing a mixture of a polysaccharide polymer with a mass percentage concentration of 1.0% to 5% and a promoter with a mass percentage concentration of 0.1% to 5% as a casting solution, and defoaming the mixture for later use; the polysaccharide polymer is any one of sodium alginate, carboxymethyl chitosan, and carboxymethyl cellulose, or a mixture of two or more thereof; the promoter is any one of molybdenum disulfide, tungsten disulfide, and cobalt disulfide, or a mixture of two or more thereof; b) preparing a mixed aqueous solution of transition metal ions constituting a redox couple as a coagulation bath, wherein the transition metal ions are Co 2+ / Ni 2+ , Cu 2+ / Mn 2+ , Fe 3+ / Mn 2+ , Fe 3+ / Cu 2+ 、Co 2+ / Cu 2+ ,La 3+ / Cu 2+ ,La 3+ / Co 2+ Any one of the following; the total mass percentage concentration of transition metal ions in the coagulation bath is 0.5% to 5%, and the molar ratio of the two transition metal ions constituting the redox couple is 1:9 to 9:1; c) selecting a high-strength hydrophilic non-woven fabric from Shijiazhuang Tianlue Industrial Fabric Co., Ltd. as a carrier, and coating the casting solution obtained in step a) on the non-woven fabric with a scraper under a winding transmission device to form a liquid film on the non-woven fabric, and then immersing the non-woven fabric coated with the film solution in the coagulation bath obtained in step b), and after sufficient cross-linking, washing away the transition metal ions on the surface with deionized water to obtain a hydrogel catalytic membrane containing diatomic sites, and winding the hydrogel catalytic membrane together for standby use; d) performing a limited water purification application on the organic pollutants through a cross-flow filtration device, the cross-flow filtration device consisting of a water pump, a pipeline, a stock liquid tank, a pressure gauge, a pressure valve and a membrane pool; cutting the hydrogel catalytic membrane containing diatomic sites obtained in step c) and loading it into the membrane pool, adding a mixed aqueous solution of organic pollutants and peroxides into the stock liquid tank; using a hydrogel catalytic membrane containing diatomic sites that can form a rich redox couple, combined with a cross-flow filtration mode, solves the problems of mass transfer limitation and catalyst fixed position. Under pressure drive, this mode only requires extremely low energy cost and extremely short reaction time to achieve rapid degradation of organic pollutants, and the degradation rate of organic pollutants reaches 60% to 100% in 2 to 5 minutes; e) dissolving the hydrogel catalytic membrane whose catalytic performance has decreased after repeated use with an aqueous sodium citrate solution, converting the transition metal ions in the hydrogel catalytic membrane into transition metal oxides by a hydrothermal reaction and separating and purifying them, dissolving them with dilute hydrochloric acid to obtain an aqueous solution of transition metal ions, and re-preparing the coagulation bath in step b), thereby realizing the recycling of resources.
2. A hydrogel catalytic membrane containing diatomic sites and its application in confined water purification as claimed in claim 1, characterized in that The peroxide is any one of hydrogen peroxide, peroxymonosulfate, peroxydisulfate and peracetic acid or a mixture of two or more thereof.
3. A hydrogel catalytic membrane containing diatomic sites and its application in confined water purification as claimed in claim 1, characterized in that The organic pollutant is any one of sulfamethoxazole, methylisothiazolinone, tetracycline, and bisphenol A, or a mixture of two or more thereof.
